(untitled) (BIRDEM Medical Journal, 2012)
The prevalence of childhood obesity has increased greatly during the past two to three decades in developed countries. With industrialization and urbanization, obesity is now becoming widely prevalent in developing countries as well. Childhood obesity is the result of persistent adverse changes in food intake, life style and energy expenditure. Although less common, there may be some underlying pathological conditions as well. Obese children and adolescents are at increased risk of having type 2 diabetes or impaired glucose tolerance, mixed features of type 1 and type 2 diabetes, hypertension, dislipidaemia, fatty liver disease, metabolic syndrome, psychosocial complications, obstructive sleep apnoea, orthopaedic problems, polycystic ovarian syndrome etc. Management of obesity need lifestyle intervention and the benefits are most likely to be achieved when diet and exercise programmes are coordinated with individual and family counseling and behaviour modification. A coordinated approach is needed involving families, school authorities, communities, healthcare providers and government to provide a continuum of population based interventions. DOI: http://dx.doi.org/10.3329/birdem.v2i2.12323 (Birdem Med J 2012; 2(2): 93-98)